A comparison of sedimentary DNA and pollen from lake sediments in recording vegetation composition at the Siberian treeline - Niemeyer, Bastian; Epp, Laura Saskia; Stoof-Leichsenring, Kathleen R. (Dr.); Pestryakova, Luidmila A. (Prof. Dr.); Herzschuh, Ulrike (Prof. Dr.) (Molecular Ecology Resources, 2017)
Reliable information on past and present vegetation is important to project future changes, especially for rapidly transitioning areas such as the boreal treeline. To study past vegetation, pollen analysis is common, while current vegetation is usually assessed by field surveys. Application of detailed sedimentary DNA (sedDNA) records has the potential to enhance our understanding of vegetation changes, but studies systematically investigating the power of this proxy are rare to date. This study compares sedDNA metabarcoding and pollen records from surface sediments of 31 lakes along a north-south gradient of increasing forest cover in northern Siberia (Taymyr peninsula) with data from field surveys in the surroundings of the lakes. sedDNA metabarcoding recorded 114 plant taxa, about half of them to species level, while pollen analyses identified 43 taxa, both exceeding the 31 taxa found by vegetation field surveys. Increasing Larix percentages from north to south were consistently recorded by all three methods and principal component analyses based on percentage data of vegetation surveys and DNA sequences separated tundra from forested sites. Comparisons of the ordinations using procrustes and protest analyses show a significant fit among all compared pairs of records. Despite similarities of sedDNA and pollen records, certain idiosyncrasies, such as high percentages of Alnus and Betula in all pollen and high percentages of Salix in all sedDNA spectra, are observable. Our results from the tundra to single-tree tundra transition zone show that sedDNA analyses perform better than pollen in recording site-specific richness (i.e., presence/absence of taxa in the vicinity of the lake) and perform as well as pollen in tracing vegetation composition.